Association of Nursing Overtime, Nurse Staffing, and Unit Occupancy with Health Care–Associated Infections in the NICU - Beltempo, Marc; Blais, Régis; Lacroix, Guy; Cabot, Michèle; Piedboeuf, Bruno (American Journal of Perinatology, 2017)
Objective This study aims to assess the association of nursing overtime, nurse staffing, and unit occupancy with health care–associated infections (HCAIs) in the neonatal intensive care unit (NICU).Study Design A 2-year retrospective cohort study was conducted for 2,236 infants admitted in a Canadian tertiary care, 51-bed NICU. Daily administrative data were obtained from the database “Logibec” and combined to the patient outcomes database. Median values for the nursing overtime hours/total hours worked ratio, the available to recommended nurse staffing ratio, and the unit occupancy rate over 3-day periods before HCAI were compared with days that did not precede infections. Adjusted odds ratios (aOR) that control for the latter factors and unit risk factors were also computed.Results A total of 122 (5%) infants developed a HCAI. The odds of having HCAI were higher on days that were preceded by a high nursing overtime ratio (aOR, 1.70; 95% confidence interval [95% CI], 1.05–2.75, quartile [Q]4 vs. Q1). High unit occupancy rates were not associated with increased odds of infection (aOR, 0.85; 95% CI, 0.47–1.51, Q4 vs. Q1) nor were higher available/recommended nurse ratios (aOR, 1.16; 95% CI, 0.67–1.99, Q4 vs. Q1).Conclusion Nursing overtime is associated with higher odds of HCAI in the NICU.
Keywords: infant; health care–associated infection; nosocomial infection; neonatal intensive care unit; nursing overtime; nurse staffing; unit occupancy